Relationship of Intellectual Intelligence Level with Santri Kepatuan in Implementing Regulations in Pondok Pesantren - Waslah Waslah; M. Roisul Mu'minin (SCHOOLAR: Social and Literature Study in Education, 2021)
The purpose of this research is to prove significantly the relationship of intellectual intelligence level with the compliance of students in carrying out regulations in Pondok Pesantren Al-Hasyim Mayangan Jogoroto Jombang. This research is quantitative research. The research sample consisted of 31 respondents, namely all students at al-Hasyim Jogoroto Jombang boarding school. In order to analyze the relationship of intellectual intelligence level with santri kepatuan in carrying out regulations. The results showed that intellectual intelligence has a positive and significant effect on the compliance of students with this can be seen from the results of the hypothesis test 0.002inate 0.05 so that it can be said that there is a relationship of the level of intellectual intelligence with the compliance of students in carrying out regulations in Pondok Pesantren Al-Hasyim Mayangan Jogoroto Jombang.